2022
DOI: 10.3934/jimo.2021042
|View full text |Cite
|
Sign up to set email alerts
|

Financing strategy selection and coordination considering risk aversion in a capital-constrained supply chain

Abstract: By applying Stackelberg game theory, this paper investigates the supply chain with a risk-neutral retailer and a risk-averse supplier, measuring risk-averse behavior by using conditional value-at-risk (CVaR). The equilibrium solutions of the supplier's wholesale price and the retailer's order quantity are obtained under two financing strategies: supplier financing (SF) and supplier investment (SI). It is found that the supplier's risk aversion is a crucial factor affecting both parties' financing decisions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…The research results indicate that combined contracts can coordinate the supply chain, but coordination can only be achieved when the manufacturer's risk aversion is low, with the manufacturer's risk aversion being an important factor in contract design and profit distribution. Kang et al (2022) investigated financing strategy selection and coordination issues in a capital-constrained supply chain between risk-neutral retailers and riskaverse suppliers. The study found that the supplier's risk aversion level critically influences the choice of financing strategy and proposes providing different financing strategy recommendations to retailers based on risk a itude and profit-sharing coefficient.…”
Section: Literaturementioning
confidence: 99%
“…The research results indicate that combined contracts can coordinate the supply chain, but coordination can only be achieved when the manufacturer's risk aversion is low, with the manufacturer's risk aversion being an important factor in contract design and profit distribution. Kang et al (2022) investigated financing strategy selection and coordination issues in a capital-constrained supply chain between risk-neutral retailers and riskaverse suppliers. The study found that the supplier's risk aversion level critically influences the choice of financing strategy and proposes providing different financing strategy recommendations to retailers based on risk a itude and profit-sharing coefficient.…”
Section: Literaturementioning
confidence: 99%
“…With the rapid development of e-commerce and network technology, supply chain competition is also gradually obvious [1]. Supply chain finance as the current enterprise survival and development have to pay attention to the link, a large number of enterprises based on their own conditions and circumstances to put forward targeted financing needs [2]. With the increase of supply chain nodes and links, the model is constantly enriched, the structure is constantly complex, the nodes of the information exchange, financial transactions, product logistics and other methods of the frequency of exchanges is increasing, the difficulty of data processing is rising [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, few scholars have studied the risk compensation effect under CGF. Cost-sharing contract claims the retailer shares a certain percentage of the supplier's production cost [23]. The revenue-sharing contract gives the supplier a percentage of the retailer's sales revenue at the end of the selling season [51].…”
mentioning
confidence: 99%